2022
DOI: 10.3390/ijms23147661
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Chloroplast Genome in Saccharum spp. and Related Members of ‘Saccharum Complex’

Abstract: High ploids of the sugarcane nuclear genome limit its genomic studies, whereas its chloroplast genome is small and conserved, which is suitable for phylogenetic studies and molecular marker development. Here, we applied whole genome sequencing technology to sequence and assemble chloroplast genomes of eight species of the ‘Saccharum Complex’, and elucidated their sequence variations. In total, 19 accessions were sequenced, and 23 chloroplast genomes were assembled, including 6 species of Saccharum (among them,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
3
13
0
Order By: Relevance
“…In contrast, the special IGS regions of the two iSNPs, namely trn G-GCC- trn M-CAU and ycf 3- trn S-GGA, were used to discriminate the three studied Salvia species. In previous studies, most of the SNPs were found in intergenic sequences, and the trn G-GCC- trn M-CAU was one of the maximum number of SNPs found four times to distinguish the six Saccharum species [ 52 ]. Meantime, the variable hotspot regions of ycf 3- trn S-GGA also can be useful as the candidate DNA barcodes for Adoxaceae and Caprifoliaceae species, and also for assessing interspecific divergence in Dipsacales species [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the special IGS regions of the two iSNPs, namely trn G-GCC- trn M-CAU and ycf 3- trn S-GGA, were used to discriminate the three studied Salvia species. In previous studies, most of the SNPs were found in intergenic sequences, and the trn G-GCC- trn M-CAU was one of the maximum number of SNPs found four times to distinguish the six Saccharum species [ 52 ]. Meantime, the variable hotspot regions of ycf 3- trn S-GGA also can be useful as the candidate DNA barcodes for Adoxaceae and Caprifoliaceae species, and also for assessing interspecific divergence in Dipsacales species [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the genetic backgrounds of the cultivars were unclear, and these markers were not informative for inferring the relationships of those species. The chloroplast genome has become an efficient option for increasing plant phylogenomics at multiple taxonomic levels over the past few years [ 33 , 34 , 35 , 36 , 37 ]. For instance, the phylogenies analyzed using the complete chloroplast genomes of three Spondias species revealed a robust phylogenetic topology for Spondias [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…robustum, S. officinarum, S. sinense, and S. barberi) of plastid genomes (Li, et al 2022) and one mitochondrial genomes from S. officinarum (Khon Kaen 3) (Shearman, et al 2016), four mitogenomes from S. hybrid (ROC22) ), FN15 , line 15a-53 , and line A1 (Zhou, et al 2022). All reported mitogenome of Saccharum spp.…”
Section: Introductionmentioning
confidence: 99%